STUDI EMPIRIS FAKTOR-FAKTOR INTERNAL INDIVIDUAL DALAM PEMBUATAN KEPUTUSAN ETIS PADA KONSULTAN PAJAK DI SEMARANG - Ika Natasya; Fuad Fuad (Diponegoro Journal of Accounting, 2021)
This study is a modification of the research of Shafer and Simmons (2008). The purpose of this study is to examine the effect of testing the influence of individual factors, namely the nature of Machiavellian, the perception of the importance of ethics and social responsibility (PRESOR), ethical considerations and ethical relativism in making ethical decisions by tax consultants.The survey method used in this study was aimed at tax consultants who worked at the Tax Consultant Office and the Public Accountant Office in the City of Semarang. The sampling technique used is non-probability sampling, namely by accidental sampling and convenience sampling. Hypothesis testing using regression analysis using the SmartPLS program.The results showed that ethical considerations and PRESORS influenced ethical decisions. In addition, the results of the study showed no influence between relativism and Machiavellianism on ethical decision making by tax consultants.